PHOTOSYNTHETIC RESPONSE OF TWO MANGO CULTIVARS SUBMITTED TO SALT STRESS AND INFECTED WITH CERATOCYSTIS FIMBRIATA - Vieccelli, Juliana Cristina; Aucique-Pérez, Carlos Eduardo; Silva Dias, Carla; Siqueira, Dalmo Lopes; Ávila Rodrigues, Fabrício (Scientia Agraria, 2018)
This study aimed to investigate the alterations on the photosynthetic performance of mango plants from cultivars Tommy Atkins and Ubá when exposed to salt stresss and infected with Ceratocystis fimbriata. Plants from these two cutivars were grown in plastic pots receiving nutrient solution with 0 and 90 mM NaCl for 50 days. At 42 days after fungal inoculation, the leaf gas exchange parameters net CO2 assimilation rate [A], stomatal conductance to water vapor [gs], internal CO2 concentration [Ci], and transpiration rate [E] as well as the lesion length, the upward and the downward relative lesion length and the radial fungal colonization were evaluated. Based on the disease variables evaluated, plants from cultivar Ubá were more resistant to infection by C. fimbriata in comparison to plants from cultivar Tommy Atkins. Lower values of A were obtained for plants from cultivar Tommy Atkins submitted to salt stress and infeted with C. fimbriata resulting, therefore, in reduced values of gs and E. In general, plants from cultivar Tommy Atkins were more affected at the photosynthetic level in comparison to plants from cultivar Ubá under salt stress and infected with C. fimbriata. Under salt stress, stomatal closure reduced the Ci values especially on plants from cultivar Tommy Atkins. Plants from cultivar Tommy Atkins were more susceptible to infection by C. fimbriata even when exposed to salt stress.